2014
DOI: 10.15381/os.v10i1.2898
|View full text |Cite
|
Sign up to set email alerts
|

Efecto antimicrobiano in vitro de la Camellia sinensis sobre bacterias orales

Abstract: Con el objeto de determinar, el efecto antimicrobiano in vitro de soluciones de Camellia sinensis (te verde) de cuatro marcas comerciales (A,B,C y D), se recolectó saliva no estimulada de 40 estudiantes universitarios y se sembró en el medio de Agar Tripticasa soya. Utilizándose el metodo de difusión por discos para las soluciones de té y los controles positivos (Amoxicilina) y negativo (agua destilada), las placas se incubaron a 37 °C /24 horas. Igual procedimiento se realizó con la Cepa de S. mutans ATCC 251… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The antimicrobial activity of green tea has been previously studied, and according to these studies, in addition to all the benefits found in this plant, the microbicidal effect is also considerable (Miller-Hamilton, 1995;Nakata et al, 2007;Setheeque, 2009). In our study, the objective was to evaluate the fungicidal effect of 20% green tea, however, for minimum inhibitory concentration and minimum fungicidal concentration assays, the extract was diluted in RPMI culture medium at a ratio of 50%, reaching a concentration of 10% which was analyzed in clinical strains of both C. albicans and non-albicans in planktonic form.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antimicrobial activity of green tea has been previously studied, and according to these studies, in addition to all the benefits found in this plant, the microbicidal effect is also considerable (Miller-Hamilton, 1995;Nakata et al, 2007;Setheeque, 2009). In our study, the objective was to evaluate the fungicidal effect of 20% green tea, however, for minimum inhibitory concentration and minimum fungicidal concentration assays, the extract was diluted in RPMI culture medium at a ratio of 50%, reaching a concentration of 10% which was analyzed in clinical strains of both C. albicans and non-albicans in planktonic form.…”
Section: Discussionmentioning
confidence: 99%
“…Susceptibility to antifungals may vary among yeast isolated from the same individual, revealing resistance to various azole antifungals. Some authors, faced with the increasing resistance to conventional antifungals, have been seeking alternatives for the treatment of oral candidiasis lesions, such as the use of herbal medicines among other alternative therapies (Vendruscolo et al, 2005;Nakata et al, 2007;Colleman, 2010;Ramage et al, 2011;Oliveira et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the amphotericin B MIC demonstrated that some non-albicans species were resistant to the analyzed antifungals, with five strains being resistant (4 to 8 μg/mL) to this antifungal. The antimicrobial activity of green tea has been previously studied, and according to these studies, in addition to all the benefits found in this plant, the microbicidal effect is also considerable (Miller-Hamilton, 1995;Nakata et al, 2007;Setheeque, 2009). In our study, the objective was to evaluate the fungicidal effect of 20% green tea, however, for minimum inhibitory concentration and minimum fungicidal concentration assays, the extract was diluted in RPMI culture medium at a ratio of 50%, reaching a concentration of 10% which was analyzed in clinical strains of both C. albicans and non-albicans in planktonic form.…”
Section: Antifungal Sensitivitiesmentioning
confidence: 99%